A new species of megastigmus (hymenoptera: Torymidae: Megastigminae) from Brazil - Doǧanlar, Mikdat; Zaché, Bruno [UNESP]; Wilcken, Carlos Frederico [UNESP] (De Gruyter, 2013)
In this paper a new parasitoid Megastigmus Dalman, 1820 (Hymenoptera: Chalcidoidea: Torymidae: Megastigminae) species was described in the subgenus Torymus, associated with the gall-forming Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae) in eucalypt plantations in Brazil.
Keywords: Brazil; Chalcidoidea; Eucalyptus camaldulensis; gall wasp entomophagous; galls; monocotyledon; new species; parasitoid; spatial distribution; wasp